Psychological Analysis of Patriotic Personality Manifestation in Students - S I Kudinov; I B Kudinova; S S Kudinov (Peoples' Friendship University of Russia (RUDN University), 2013)
The psychological determinants and the peculiarities of patriotic personality manifestation in students are analyzed in the article in the frame of the system paradigm and on the basis of the disposition conception of personality and character characteristics.